2013
DOI: 10.1080/10357823.2013.853167
|View full text |Cite
|
Sign up to set email alerts
|

“Middling” Chinese Returnees or Immigrants from Canada? The Ambiguity of Return Migration and Claims to Modernity

Abstract: This paper investigates the conceptual overlaps between transnational return migration and immigration by drawing on a qualitative study of Mainland Chinese return migration from Canada. The paper argues that reframing return migration as a distinct type of immigration draws attention to the citizenship vulnerabilities experienced by "middling" returnees who are not privy to the preferential treatment given to highly skilled returnees. They come to be considered as "foreigners" in their homeland because they h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…It comprises ‘returning Scots’ who have come back to Scotland; ‘new Scots’ who are about to leave Scotland; ‘live diaspora’ comprising individuals who were born in Scotland or have worked or studied in Scotland and are now living outside of Scotland; ‘ancestral diaspora’ which refers to individuals of Scottish descent; and ‘ affinity diaspora’ incorporating individuals with a direct or indirect connection to Scotland but with no genealogical link to the country (Ancien et al ., ). Similarly, in a report written for the Asia Pacific Foundation concerning Canada's emerging diaspora strategy, Boyle and Kitchin () recommend that former immigrants and overseas students are a potential diaspora resource for the country (also see Ho & Ley, ). Like these countries, Singapore experiences considerable immigration but the definition of the Singaporean diaspora limits cultural inclusion to those that consider it their natal country or who have legal status as permanent residents or citizens.…”
Section: Reflections On Singapore's Diaspora Strategies To Datementioning
confidence: 99%
See 1 more Smart Citation
“…It comprises ‘returning Scots’ who have come back to Scotland; ‘new Scots’ who are about to leave Scotland; ‘live diaspora’ comprising individuals who were born in Scotland or have worked or studied in Scotland and are now living outside of Scotland; ‘ancestral diaspora’ which refers to individuals of Scottish descent; and ‘ affinity diaspora’ incorporating individuals with a direct or indirect connection to Scotland but with no genealogical link to the country (Ancien et al ., ). Similarly, in a report written for the Asia Pacific Foundation concerning Canada's emerging diaspora strategy, Boyle and Kitchin () recommend that former immigrants and overseas students are a potential diaspora resource for the country (also see Ho & Ley, ). Like these countries, Singapore experiences considerable immigration but the definition of the Singaporean diaspora limits cultural inclusion to those that consider it their natal country or who have legal status as permanent residents or citizens.…”
Section: Reflections On Singapore's Diaspora Strategies To Datementioning
confidence: 99%
“…For the case of Singapore, the other author conducted ethnographic research and interviews with overseas Singaporeans in London from 2004 to 2005 (Ho, 2008; 2009). In combination, the authors have conducted research on the diaspora strategies of Armenia, China, Canada, Ireland, Latvia, Scotland and Singapore (e.g., Boyle & Kitchin, 2008; 2011; Ho, ; Ho & Ley, ). Further informing this paper are analyses of newspaper articles, websites and government publications about the Singaporean diaspora.…”
Section: Introductionmentioning
confidence: 99%
“…While many of these migrants return to Hong Kong for economic reasons, they still want to move back to Vancouver (especially after retirement) to seek the quality of life they desire (Ley and Kobayash 2005, 121). Likewise, Ho and Ley (2014) also found that many returnees to mainland China develop a strong identification with Canada and perceive themselves as part of the Canadian diaspora. As Ho and Ley (2014, 44) indicate, 'returnees seek contact with native English-speaking Canadians who are seen to embody not only fluent language skills, but also cultural competencies as 'real Canadians' (a term used frequently by returnees), however loosely this is defined'.…”
Section: Research On Ageing and Return Migrationmentioning
confidence: 91%
“…Conventional wisdom suggests that even if immigrants experience deskilling in the labor market, the earning potential of such temporary jobs may still enable savings and investments that could lead to higher social status back home. Recent studies of middling returnees, however, indicate that they may find themselves struggling to fit in upon return, with fewer resources than their peers who qualify for government benefits and home-country networks (Ho and Ley, 2014). Studies of student-migrants-who in some cases undertake transient jobs due to an immigration status which may preclude exploration of preferred career options-show that a series of temporary jobs may have an entrapment effect on student migrants that prevent them from accessing the labor markets once they earn their degrees (Luthra and Plath, 2016).…”
Section: Middling Through Transnational Transiencymentioning
confidence: 99%